Approaches for Vehicle Cyber-Security in the US - Hirofumi Onishi; Kelly Wu; Kazuo Yoshida; Takeshi Kato (International Journal of Automotive Engineering, 2017)
Recently, cyber-risks in modern intelligent vehicles have become concerns to society. First, carry-in devices, such as smart-phones and USB-memory-devices used outside of vehicles expose vehicles to various cyber-attacks from the external IT (Information Technology) world. Next, Global Navigation Satellite Systems (GNSS) which provide position information to many valuable functions have vulnerabilities to jamming and spoofing. Finally, emerging vehicle-to-vehicle communication poses security challenges, because of its unique communication schema where all neighboring vehicles exchange data within a short duration. In this report, we examine these vulnerabilities’ impact on vehicle cyber-security and introduce various countermeasures against these vulnerabilities in the US.